A Utilitarian Evaluation of Public Transportation's Role in Reducing Air Pollution and Enhancing Societal Well-Being - Wu, Rebecca Angela (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
This thesis examines the ethical and practical role of public transport in reducing air pollution through the lens of John Stuart Mill’s utilitarianism, with a focus on its contribution to public well-being. Using a literature review of academic studies, government reports, and international publications, the research analyzes both quantitative indicators—such as air quality improvements and emission reductions—and qualitative aspects, including public perception of Jakarta’s LRT system. The findings show that the LRT produces a significantly lower carbon footprint per passenger compared to private vehicles and is linked to improved physical and mental well-being for users. Although public perception toward affordability is positive, concerns remain regarding safety, comfort, and connectivity, suggesting that the system requires further development and supporting policies to achieve lasting impact. From Mill’s utilitarian perspective, public transport aligns with efforts to maximize overall societal happiness by reducing pollution and promoting collective welfare. Nonetheless, structural constraints and mixed public perceptions influence its real-world effectiveness. Despite these challenges, the study concludes that public transport remains a highly promising solution for mitigating urban air pollution and advancing public well-being.